Inhibition of NOX2 or NLRP3 inflammasome prevents cardiac remote ischemic preconditioning - Benavides, Sandra; Palavecino, Rodrigo; Riquelme, Jaime A.; Montecinos, Luis; Finkelstein, José Pablo; Donoso, Paulina; Sánchez, Gina (Frontiers in Physiology, 2024)
Introduction. Short episodes of ischemia-reperfusion (IR) in the heart (classical ischemic preconditioning, IPC) or in a limb (remote ischemic preconditioning, RIPC) before a prolonged ischemic episode, reduce the size of the infarct. It is unknown whether IPC and RIPC share common mechanisms of protection. Animals KO for NOX2, a superoxide-producing enzyme, or KO for NLRP3, a protein component of inflammasome, are not protected by IPC. This study aimed to investigate if NOX2 or NLRP3 inflammasome are involved in the protection induced by RIPC. Methods. We preconditioned rats using 4 x 5 min periods of IR in the limb with or without a NOX2 inhibitor (apocynin) or an NLRP3 inhibitor (Bay117082). In isolated hearts, we measured the infarct size after 30 min of ischemia and 60 minutes of reperfusion. In hearts from preconditioned rats we measured the activity of NOX2; the mRNA of Nrf2, gamma-glutamylcysteine ligase, glutathione dehydrogenase, thioredoxin reductase and sulfiredoxin by RT-qPCR; the content of glutathione; the activation of the NLRP3 inflammasome and the content of IL-1β and IL-10 in cardiac tissue. In exosomes isolated from plasma, we quantified NOX2 activity.Results. The infarct size after IR decreased from 40 % in controls to 9 % of the heart volume after RIPC. This protective effect was lost in the presence of both inhibitors. RIPC increased NOX2 activity in the heart and exosomes, as indicated by the increased association of p47phox to the membrane and by the increased oxidation rate of NADPH. RIPC also increased the mRNA of Nrf2 and antioxidant enzymes. Also, RIPC increased the content of glutathione and the GSH/GSSG ratio. The inflammasome proteins NLRP3, procaspase-1, and caspase-1 were all increased in the hearts of RIPC rats. At the end of RIPC protocol, IL-1β increased in plasma but decreased in cardiac tissue . At the same time, IL-10 did not change in cardiac tissue but increased by 70% during the next 50 minutes of perfusion. Conclusions. RIPC activates NOX2 which upregulates the heart's antioxidant defenses and activates the NLRP3 inflammasome which stimulates a cardiac anti-inflammatory response. These changes may underlie the decrease in the infarct size induced by RIPC.